2011
DOI: 10.1021/jf2009556
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Activities of Adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) on the Growth of the Stomach Cancer AGS Cell Line and Indomethacin-Induced Gastric Ulcers

Abstract: Adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) seeds have long been used to treat warts, chapped skin, rheumatism, and neuralgia in traditional Chinese medicine (TCM). Recently, studies demonstrated its anti-inflammatory, antiproliferative, antitumor, and antiallergic activities. In the present study, we first report the gastroprotective effects of dehulled adlay (DA) seeds, which consist of bran (AB) and endosperm (AE). The DA ethanolic extract (DAE) was prepared, along with the AB and AE ethanolic extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 26 publications
0
42
1
3
Order By: Relevance
“…Job's tears are taken by people due to its beneficial effect for hay fever, high cholesterol, cancer, warts, obesity, arthritis, allergic disorder and respiratory tract infections. Many scholars have reported different biological activities of Job's tears, including antioxidant/free radical scavenging [12], anti-inflammatory [13,14], anti-tumor [12,15,16], hypolipidemic [17], hypocholesterolemic [18], anti-allergic [19,20], hypoglycemic [21], antiobesity [22], anti-mutagenic [23], anti-ulcer [24], prebiotic activity [25], hormonal modulation [26], osteoporosis preventing [27], abortifacient [28] and antimicrobial effect [29].…”
Section: Introductionmentioning
confidence: 99%
“…Job's tears are taken by people due to its beneficial effect for hay fever, high cholesterol, cancer, warts, obesity, arthritis, allergic disorder and respiratory tract infections. Many scholars have reported different biological activities of Job's tears, including antioxidant/free radical scavenging [12], anti-inflammatory [13,14], anti-tumor [12,15,16], hypolipidemic [17], hypocholesterolemic [18], anti-allergic [19,20], hypoglycemic [21], antiobesity [22], anti-mutagenic [23], anti-ulcer [24], prebiotic activity [25], hormonal modulation [26], osteoporosis preventing [27], abortifacient [28] and antimicrobial effect [29].…”
Section: Introductionmentioning
confidence: 99%
“…1 Cutaneous vasculitis induced by HZ is a rare event and may appear at the site of previous and healed HZ eruption, 2 which is an example of Wolf's isotopic response. 3,4 However, the case reported by Wollina and Sch€ onlebe is different and, to the best of our knowledge, unique in that the HZ-related disorder (vasculitis) preceded the outbreak of herpetic lesions in the same dermatome. Interestingly, vasculitis was mainly located on the distal segment, while HZ appeared on the proximal segment of the dermatome.…”
Section: Segmental Immune Disorders Related To Herpes Zostermentioning
confidence: 80%
“…Coix lacrymajobia major component of Ibane â , known colloquially as Job's tears, coixseed, or adlaihas long been used in Nowadays, many studies have demonstrated that Coix lacryma-jobi has anti-inflammatory, antiproliferative, antitumor, and antiallergic activities. [3][4][5] Currently, Coix lacryma-jobi is approved by the Korean Food and Drug Administration based on the theoretical backgrounds of Korean traditional herbal medication, and today it is widely used in over-the-counter settings throughout Korea. Nitric oxide or superoxide overproduction by activated macrophages is believed to be critically involved in both acute and chronic inflammation.…”
mentioning
confidence: 99%
“…Coix extract was found to produce dose‐dependent gastroprotection against indomethacin. This effect was at least partially because of antioxidant actions of the phenolic acids in Coix (Chung et al, ). A methanol extract of Coix seeds was found to reduce nitric oxide and superoxide production in RAW 264.7 macrophages (Seo et al, ).…”
Section: Discussionmentioning
confidence: 99%